2013
DOI: 10.1002/clen.201100719
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Optimization of Activated Carbon Production from Agave sisalana and Punica granatum Peel: Adsorbents for C.I. Reactive Orange 4 Removal from Aqueous Solution

Abstract: In the present study, activated carbons were prepared from sisal fiber (Agave sisalana sp.) and pomegranate peel (Punica granatum sp.) using phosphoric acid as the activating agent. Both sisal fiber activated carbon (SFAC) and pomegranate peel activated carbon (PPAC) were characterized using methylene blue number, iodine number, BET surface area, SEM, and FTIR. The BET surface area of the SFAC and PPAC were 885 and 686 m2/g, respectively. The adsorption studies using C.I. Reactive Orange 4 dye on the SFAC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…In a recent study, Senthilkumar et al [25] reported the use of activated carbon produced from Punica granatum peel to remove C.I. Reactive Orange 4 from aqueous solutions.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…In a recent study, Senthilkumar et al [25] reported the use of activated carbon produced from Punica granatum peel to remove C.I. Reactive Orange 4 from aqueous solutions.…”
Section: Desalination and Water Treatmentmentioning
confidence: 99%
“…Besides these, several other researchers also examined the suitability of different fruits and vegetables waste peels as adsorbents for the removal of aquatic pollutants [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171]. Tables 6 and 7 represent uptake capacities of various peel-based adsorbents for metals and organic pollutants removal from water, respectively.…”
Section: The Adsorption Of Methylene Blue (Mb) and Acid Orange 7 (Ao7mentioning
confidence: 99%
“…According to Giles classification, the isotherms belong to the L type however, for the GC carbon it is L2 whereas for C, CPP, CPS carbons the type L4 is observed. The L2 class of isotherms is commonly reported for the adsorption of phenols from aqueous solution [16,21,28,[33][34][35][36]. This is the case when no strong competition between the adsorbate and the solvent for occupying the adsorption sites is observed.…”
Section: Equilibrium Adsorption Of Phenolmentioning
confidence: 98%
“…Despite the fact that in literature many different equations [33,37,[40][41][42][43][44] isotherms, in this work only the Langmuir (Eq. (2)) and Freundlich (Eq.…”
Section: Equilibrium Adsorption Of Phenolmentioning
confidence: 99%
See 1 more Smart Citation